STUDENT SELF-GOVERNMENT AS AN IMPORTANT CONDITION FOR DEMOCRATIZATION OF HIGHER EDUCATION (Pedagogy of Higher and Secondary Education, 2011)
The state of study of problem of becoming and development of student self-goverment is considered on territory of the Ukrainian state, contradictions of this phenomenon are certain.
Keywords: student self-goverment; democratization; higher school; upbringing of students